Fenologia da frutificação e síndromes de dispersão em uma comunidade de Cerrado - Oliveira, Ana Paula de Assis (2004)
The dispersai modes and the fruiting phenology were studied in a Cerrado (sensu strictu) community in Uberlândia, Minas Gerais, from April 2002 to July 2003. A total of 89 species, belonging to 29 families and 70 genera, was recorded. The fruits were classified into composed (1.12%), multiple (5.61%) and simple (93.25%) with nine subdivisions. The subtype berry (21.34%) was the most abundant. Zoochory was the main dispersai mode (55.06%) followed by anemochory (28.08%) and autochory (16.58%). The zoochorous species fruit during all the year with a peak at the wettest and warmest season. The fruiting rhythm was positively correlated with temperature (rs = 0.707, p = 0.002) and precipitation (rs = 0.792, p = 0.0003). The anemochorous species were less frequent in the warmest (rs = -0.565, p = 0.022) and most humid (rs = -0.634, p = 0.008) months, fruiting predominantly in winter. Zoochory was the main dispersai mode in low scrub, schrubs and trees. All herbs were zoochory. Anemochory was the main mode in lianas. The results of this study indicate that the disponibility of the zoochorous species during all the year seems to be influenced by the dispersers agents that feed on them; the fruiting rhythm of wind- dispersed species, however, seems to be more influenced by abiotic factors like low precipitation and strong winds that favour seed dispersai